2000
DOI: 10.1093/genetics/155.1.309
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Genetics of Nucleotide Binding Site-Leucine Rich Repeat Resistance Gene Homologues in the Genomes of Two Dicotyledons: Tomato and Arabidopsis

Abstract: The presence of a single resistance (R) gene allele can determine plant disease resistance. The protein products of such genes may act as receptors that specifically interact with pathogen-derived factors. Most functionally defined R-genes are of the nucleotide binding site-leucine rich repeat (NBS-LRR) supergene family and are present as large multigene families. The specificity of R-gene interactions together with the robustness of plant-pathogen interactions raises the question of their gene number and dive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2000
2000
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 188 publications
(3 citation statements)
references
References 79 publications
0
1
0
Order By: Relevance
“…M-82 is a red fruited, determinate, processing-type tomato. The genetic constitutions of the 50 ILs, as well as 26 sublines were described by Pan et al (2000). The sublines were obtained as the product of backcrossing selected introgressed lines with M-82, creating smaller introgressed sections.…”
Section: Plant Materials and Experimental Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…M-82 is a red fruited, determinate, processing-type tomato. The genetic constitutions of the 50 ILs, as well as 26 sublines were described by Pan et al (2000). The sublines were obtained as the product of backcrossing selected introgressed lines with M-82, creating smaller introgressed sections.…”
Section: Plant Materials and Experimental Trialsmentioning
confidence: 99%
“…Due to overlapping introgressions, effects observed in only one line of two overlapping segments can be ascribed to the unshared region. The L. pennellii ILs thus subdivide the tomato genome into 107 ''bins'' (Pan et al 2000). Bin locations are referred to by chromosome number followed by letter identifying the bin.…”
Section: Plant Materials and Experimental Trialsmentioning
confidence: 99%
“…Solyc06g008760.1.1 (Log 2 Fc = −3.05; tomato Glutaredoxin-C13-like ) has been demonstrated to be upregulated in ripening inhibitor ( rin ) mutants of S. lycopersicum ( Kumar et al, 2016 ). Solyc07g055610.2.1 (Log 2 Fc = −2.05); tomato Resistance protein R1) has been related to resistance to late blight ( Bournival et al, 1989 ) and it has been shown to be linked to proteinase inhibitor I3 upon Fusarium oxysporum infection ( Bournival et al, 1989 ; Pan et al, 2000 ). Solyc01g010480 (Log 2 Fc = −2.2; tomato K+ channel KAT1) was demonstrated to be highly upregulated in low K tolerant tomato genotypes upon potassium deficiency ( Zhao et al, 2018 ).…”
Section: Resultsmentioning
confidence: 99%